2022
DOI: 10.1007/s12272-021-01367-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of BRL-50481 on ovalbumin-induced asthmatic lung inflammation exacerbated by co-exposure to Asian sand dust in the murine model

Abstract: Asian sand dust (ASD), which mainly originates in China and Mongolia in the spring and blows into Korea, can exacerbate respiratory and immunological diseases. This study aims to observe effects of co-exposure to ASD on ovalbumin (OVA)-induced asthmatic lung inflammation and of treatment with a phosphodiesterase 7 (PDE7) inhibitor in a mouse model. The challenge with OVA increased airway hyperresponsiveness (AHR) and inflammatory cell infiltration into the lung tissue. Interleukin (IL)-13, tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…As a result, Roflumilast, a selective and long-acting PDE4 inhibitor, was developed as a treatment of inflammatory lung diseases such as asthma and COPD for preventing their exacerbation (Ilango et al 2013). Our previous study also showed that PDE7 inhibitor, BRL-50481, alleviates ovalbumin-induced asthmatic lung inflammation (Kim et al 2022).…”
Section: Introductionmentioning
confidence: 83%
“…As a result, Roflumilast, a selective and long-acting PDE4 inhibitor, was developed as a treatment of inflammatory lung diseases such as asthma and COPD for preventing their exacerbation (Ilango et al 2013). Our previous study also showed that PDE7 inhibitor, BRL-50481, alleviates ovalbumin-induced asthmatic lung inflammation (Kim et al 2022).…”
Section: Introductionmentioning
confidence: 83%
“…A potential solution to the lack of efficacy could be directing drug development efforts to evaluate combinatory regimens, as suggested for PDE 5 inhibitors in ED; combining PDE 5 inhibitors with other therapeutic approaches, such as antioxidants, showed improved outcomes without increasing ADRs (Mykoniatis et al, 2021). A similar strategy is suggested Frontiers in Pharmacology frontiersin.org Alzheimer's disease (Li et al, 2018) BRL-50481 GlaxoSmithKline PDE 7 CNS disorders (Chen et al, 2020), inflammation (Kim et al, 2022) CC-3052 Celgene PDE 4 Tuberculosis , HIV (Guckian et al, 2000;La Maestra et al, 2000) EHNA N/A PDE 2 Cancer (Bernard et al, 2014;Hiramoto et al, 2014;Murata et al, 2019), HIV (Sei et al, 1989) JNJ-42314415…”
Section: Discussionmentioning
confidence: 99%
“…Several agents target novel PDE targets. BRL-50481, a PDE 7 inhibitor, have showed neuroprotector ( Chen et al, 2020 ) and anti-inflammatory properties ( Kim et al, 2022 ) on animal models. Lu AF33241, a dual PDE 2A/PDE 10A inhibitor, was found to attenuate sub-chronic phencyclidine-induced deficits in novel object recognition and displayed antipsychotic-like activity ( Redrobe et al, 2015 ).…”
Section: Phosphodiesterase Inhibitors In Clinical Researchmentioning
confidence: 99%
“…After the experiment, blood was collected from the inferior vena cava of all mice, and 40 μL 3.2% sodium citrate was used as an anticoagulant for each syringe. The blood samples were centrifuged at 1,500 g and 4°C for 10 min, and the separated serum was stored at −80°C for the determination of OVA-specific immunoglobulin E (IgE) and IgG1 protein levels [24]. Mice were euthanized by intraperitoneal injection of 200 mg/kg pentobarbital sodium, and bronchoalveolar lavage fluid (BALF) was collected from all the mice for cell count and cytokine detection.…”
Section: Establishment Of the Allergic Asthmatic Mouse Model And Grou...mentioning
confidence: 99%
“…The precipitate was collected and resuspended with 250 μL PBS, and the total number of inflammatory cells in BALF was counted using a blood cell counter (Paul Marienfeld GmbH & Co. KG, Lau-da-Konigshofen, Germany). After the cytocentrifuge preparation with Cytospin 2 (Thermo Fisher), differential cell counts were performed using staining images prepared with the Kwik-Dif TM Stain kits based on standard morphological criteria (Thermo Fisher) [24].…”
Section: Balf Collection and Cell Countmentioning
confidence: 99%